PERKAWINAN MUSLIM DENGAN AHLULKITAB - Afrian Raus (JURIS (Jurnal Ilmiah Syariah), 2017)
This article discusses marriage between Moslems and ahlulkitab  viewed from Islamic law perspectives. It emphasizes that such marriage is illegal and consequently marrying ahlulkitab is definitely prohibited since they are non believers which is pointed out by The Quran in Surah Al-Baqarah. In addition, In Surah al-Maidah, the word ahlul kitab is longer found since the revised their the Bible and changed the idea of monotheism into the concept of Trinity which regards Uzain and Isa as the sons of God and do not accept Muhammad SAW as the prophet as well.